Á mão livre: explorando narrativas visuais de alunos brasileiros sobre a aprendizagem de Inglês - Marina Morena dos Santos e Silva (2017)
This dissertation aims to investigate English language learning represented in freehand visual narratives made by secondary school students from a private school in the city of Santa Luzia. This research is grounded on the concepts of Social Semiotics (HODGE; KRESS, 1988;KRESS, 1997, 2010), Multimodality (KRESS, 1997, 2010), Grammar of Visual Design (KRESS; VAN LEEUWEN, 2006 [1996]) and on contemporary theories about metaphor (LAKOFF; JOHNSON, 1980 [2003]; KÖVECSES 2002; FORCEVILLE, 2010) and its interface with other phenomena (BARCELONA, 2003a, 2003b; RADDEN, 2003a, 2003b;PAIVA, 2010b, 2011a). The concept of representation is taken from the previous theories, complementing rather than excluding each other. Together, they see representation as a cognitive process related to past experiences and to historical, social and psychological experiences of its producer. A qualitative approach is followed in order to analyse and present the findings; however, some quantitative analysis is also carried out. Thirty-five drawings made by the learners themselves are analysed based on visual content analysis (BARDIN, 2011; PENN, 2002), which is supported by grids of variants and values (BELL, 2001), and follows the Grammar of Visual Design categories (KRESS; VAN LEEUWEN, 2006[1996]), and the Multimodal Metaphor theory (FORCEVILLE, 2010). Our analysis showed that English language learning, in this context, can be understood through five groupings: (1) English language and globalisation; (2) mediating elements; (3) learning context; (4) practicecommunities; and (5) English language use. The findings point out that the participants portray themselves as protagonists not only of their own stories, but also of their learning, which is mainly seen as social practice, mediated by social interactions and cultural artefacts. The learners reveal to seek for meaningful opportunities to use the foreign language in moreexpressing contexts and even in immersion contexts. Yet, the language is taken as a symbolic good, which allows the gaining of other goods, as well as shows ideas of upward mobility tied to the language learning. The contributions of this research to Applied Linguistics rely on theunderstanding of the discourse instantiated in different codes, as well as in the access to a critical analysis of ideologies and beliefs which, at the same time, are maintained, reinforced and spread out through visual representations. The visual narratives analysed are an importanttool in the investigation of the process of learning and teaching; they can provide for a reflexive process and describe not only subjective experiences, but also a system of meaningmaking, socially and culturally built.